2019
DOI: 10.3122/jabfm.2019.04.180272
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Family Medicine Transitional Care Service Line

Abstract: As of 2013, the all-cause readmission rate among Medicare fee-for-service beneficiaries was 17.5%. In addition to poor outcomes, 30-day hospital readmissions account for over $17 billion in Medicare expenditures. The presence and involvement of a primary care provider can be essential during the transition period from hospital discharge to the outpatient setting. Objective: In an effort to reduce 30-day hospital readmissions a transitional care management (TCM) service was implemented in a multi-site family me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Farford et al 20 used methods previously shown to prevent readmissions, and added some. The authors found that their attempts did not decrease readmissions further, but were sufficiently worthwhile to continue using.…”
Section: Additional Topicsmentioning
confidence: 99%
“…Farford et al 20 used methods previously shown to prevent readmissions, and added some. The authors found that their attempts did not decrease readmissions further, but were sufficiently worthwhile to continue using.…”
Section: Additional Topicsmentioning
confidence: 99%
“…A lack of prompt PCP follow-up (within 4 weeks after discharge) has been shown to be linked to an increased risk of hospital readmission for the same condition and is likely to lead to a longer hospital stay. Patients are more likely to experience unfavorable outcomes following discharge if prescription mistakes, inadequate follow-up on unfinished tests, or lost opportunities for advised testing or outpatient procedures are present (Farford et al, 2019;Misky et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A lack of prompt PCP follow-up (within 4 weeks after discharge) has been shown to be linked to an increased risk of hospital readmission for the same condition and is likely to lead to a longer hospital stay. Patients are more likely to experience unfavorable outcomes following discharge if prescription mistakes, inadequate follow-up on unfinished tests, or lost opportunities for advised testing or outpatient procedures are present (11,12).…”
Section: Introductionmentioning
confidence: 99%